The Effect of Lower Limb Blood Flow Restriction on the Physiological Intensity and Neuromuscular Fatigue Characteristics of Different Stance Taijiquan Practice - Li, Yuxi; Deng, Jianfeng; Wang, Zhenyu; Yin, Mingyue; Li, Yongming (The Journal of the International Society of Chinese Health Practices, 2024)
See PDF for details